The Effect Of Emotional Intelligence, Work–Life Balance, And Job Satisfaction On Employee Engagement Among Generation Z Workers In Denpasar - Ni Putu Intan Lestari; I Gusti Ngurah Widya Hadi Saputra; Ketut Elly Sutrisni; I Putu Dharmawan Pradhana (Pascasarjana STIE Amkop Makassar, 2026)
Employee engagement is essential for sustaining organizational performance, particularly among Generation Z employees who have distinct work expectations and values. The rapid growth of the service and tourism sector in Denpasar requires organizations to understand key psychological and organizational factors that foster engagement among young workers. Emotional Intelligence, Work Life Balance, and Job Satisfaction are considered important resources within the Job Demands Resources framework that can strengthen motivation and work involvement.This study examines the influence of Emotional Intelligence, Work Life Balance, and Job Satisfaction on Employee Engagement among Generation Z employees in Denpasar. A quantitative explanatory approach was used, with data collected through structured questionnaires from employees in the service and tourism industries. Multiple regression analysis was applied to assess both partial and simultaneous relationships among the variables.The results show that Emotional Intelligence, Work Life Balance, and Job Satisfaction positively affect Employee Engagement, with Work Life Balance emerging as the most influential factor. This reflects Generation Z’s strong preference for flexibility and psychological well-being. Emotional Intelligence enhances resilience and interpersonal effectiveness, while Job Satisfaction strengthens motivation and attachment to work. These findings highlight the importance of integrating personal capabilities and supportive organizational practices to enhance engagement among Generation Z employees.